2021
DOI: 10.1111/geb.13323
|View full text |Cite
|
Sign up to set email alerts
|

Conditional love? Co‐occurrence patterns of drought‐sensitive species in European grasslands are consistent with the stress‐gradient hypothesis

Abstract: Aim The stress‐gradient hypothesis (SGH) postulates that species interactions shift from negative to positive with increasing abiotic stress. Interactions between species are increasingly being recognized as important drivers of species distributions, but it is still unclear whether stress‐induced changes in interactions affect continental‐to‐global scale species distributions. Here, we tested whether associations of vascular plant species in dry grasslands in Europe follow the SGH along a climatic water defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…More generally, differences in species-specific grouping propensities (Fig. 2 ) indicate strong context dependence when assessing the impact of environmental variables on community structure and underscore the importance of choosing a species’ lens for disentangling relationships between grouping patterns of multiple organisms and environmental gradients 48 , 49 . Not accounting for species identity could bias relationships between grouping patterns and environmental variables (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, differences in species-specific grouping propensities (Fig. 2 ) indicate strong context dependence when assessing the impact of environmental variables on community structure and underscore the importance of choosing a species’ lens for disentangling relationships between grouping patterns of multiple organisms and environmental gradients 48 , 49 . Not accounting for species identity could bias relationships between grouping patterns and environmental variables (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interspecific spatial associations can arise from species interaction, response to environmental covariates, and common dispersal barriers ( Blanchet et al, 2020 ; de Jonge et al, 2021 ; Poggiato et al, 2021 ). Our context-dependent JSDM, which accounts for similarities and disparities in species-specific response to habitat covariates considered relevant to medium- and large-bodied mammal species, detected a higher prevalence of interspecific spatial associations in human-disturbed habitats.…”
Section: Discussionmentioning
confidence: 99%
“…When a clear community mechanism is analyzed, it is conducive to policy formulation at the current stage and future maintenance and management. Melinda et al (2021) [24] found that the interaction between species is increasingly recognized as an important driving factor for the distribution of species, but it is not clear whether changes in the interaction caused by pressure will affect the distribution of species [23].…”
Section: Identifying Indicator Speciesmentioning
confidence: 99%